2005
DOI: 10.1177/0011128705277784
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mandatory Arrest Policies, Police Organizational Characteristics, and Situational Variables on the Probability of Arrest in Domestic Violence Cases

Abstract: Prior research into factors predicting arrest in domestic violence cases is limited in three regards: (a) no examination of whether mandatory arrest policies are associated with increased risk of arrest across multiple jurisdictions; (b) little consideration of whether police organizational characteristics influence arrest in such cases; and (c) little examination of whether mandatory arrest policies moderate the influence of extralegal characteristics on arrest risks. Using year 2000 data from the National In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
192
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(209 citation statements)
references
References 51 publications
15
192
2
Order By: Relevance
“…more likely to arrest if they are not married (Belknap, 1995), while other studies have found the opposite (Dichter, Marcus, Morabito, and Rhodes, 2011). Other studies have focused on police organizational factors (Chappell, MacDonald, & Manz, 2006;Eitle, 2005;Finn, Blackwell, Stalans, Studdard, & Dugan, 2004) and community factors (Logan, Walker, and Leukefeld, 2001). …”
Section: Ipamentioning
confidence: 99%
See 1 more Smart Citation
“…more likely to arrest if they are not married (Belknap, 1995), while other studies have found the opposite (Dichter, Marcus, Morabito, and Rhodes, 2011). Other studies have focused on police organizational factors (Chappell, MacDonald, & Manz, 2006;Eitle, 2005;Finn, Blackwell, Stalans, Studdard, & Dugan, 2004) and community factors (Logan, Walker, and Leukefeld, 2001). …”
Section: Ipamentioning
confidence: 99%
“…Most studies have confirmed that incident-level factors appear to have the most impact on police response. Specifically, the more severe the violence, if there are injuries, and if there is a weapon present (Bachman & Coker, 1995;Belknap, 1995;Eitle, 2005). Other studies have found conflicting findings on extralegal factors influencing police arrest.…”
Section: Ipamentioning
confidence: 99%
“…Many factors contributed to the adoption of such policies: a grass-roots battered women's movement pressed for legislative changes that would facilitate or compel law enforcement to invoke the law against offenders (Ferraro 1989); the threat of litigation against police departments; recommendations by the Attorney General's Task Force on Family Violence; and the findings of the Minneapolis domestic violence experiment, which concluded that repeat violence was less likely when police made arrests (Sherman and Cohn 1989). Pro-arrest policies have increased the incidence of arrests in cases of spousal assault, though compliance by officers is only partial (Cross and Newbold 2010;Eitle 2005;Ferraro 1989;Hirschel et al 2007; Jones and Belknap 1999). Evidence from replications of the Minneapolis experiment have cast doubts on the conclusions that were drawn from that study, but it is doubtful that many departments have abandoned pro-arrest policies, which are still expected by sovereigns.…”
Section: Perspectives On Police Organiz Ationsmentioning
confidence: 99%
“…Current research indicates that the passage of mandatory and preferred arrest domestic violence laws has resulted in an increased likelihood of arrest in cases of domestic violence (see, e.g., Chaney & Saltzstein, 1998;Eitle, 2005;Ho, 2000;Lawrenz, Lembo & Schade, 1988;Miller, 2001Miller, , 2005; Municipality of Anchorage, 2000: 8-9; Office of the A.G. California, 1999;Robinson & Chandek, 2000;Simpson, Bouffard, Garner and Hickman, 2006;Wanless, 1996, pp. 558-9;and Zorza & Woods, 1994, p.12).…”
Section: Law Prior Researchmentioning
confidence: 99%